Doing Well versus Doing Good: The Differential Effect of Underdog Positioning on Moral and Competent Service Providers - Kirmani, Amna; Hamilton, Rebecca W.; Thompson, Debora V.; Lantzy, Shannon (Journal of Marketing, 2017)
This research examines how consumers make trade-offs between highly competent, less moral service providers and highly moral, less competent service providers. Counter to research on general impression formation, which shows that moral traits dominate competence traits, the authors demonstrate that when choosing between service providers, consumers systematically value competence more than morality. However, underdog positioning moderates this effect. When a moral service provider is positioned as an underdog, consumers feel empathy, thereby attenuating the dominance of competence. Notably, although underdog positioning can help a moral provider overcome a deficit in competence, it does not help a competent service provider overcome a deficit in morality or a warm provider overcome a deficit in competence. Thus, underdog positioning is particularly well suited for less competent service providers who are highly moral.